(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the drug use structure and analyze the list of drugs used at Thai Binh Pediatric Hospital in 2020 according to ABC, VEN and ABC/VEN methods. Subjects and Method: A cross-sectional study 202 drug items were used at Thai Binh Pediatric Hospital in 2020 (January 1, 2020-December 31, 2020). Result: 202 drug items worth VND 19,168 billion with 9 main groups of physical exercise. Group of antiparasitic drugs and antibiotics with 51 drug items (25.25%) with a value of 11,584 billion VND (60.44%). Drugs acting on the respiratory systerm 13 drug items (6.44%) with a value of 2,892 billion VND (15.09%). Locally produced drugs 100 km with a value of 6.2 billion VND (32.56%). Imported drugs 102km with a value of 12.9 billion VND (67.44%). Single-ingredient drug 185 drug items (91.58%) with a value of 17.02 billion VND (88.84%). Multi-component drug 17 KM (8.42%) with a value of 2.13 billion VND (11.16%). Generic drug 185 KM (91.58%) with a value of 12.36 billion VND (64.51%). Original brand name drug 17 KM (8.42%) with a value of 6.8 billion VND (35.49%). Drugs used by injection 108 KM (53.47%) with a value of 15.3 billion VND (79.93%). The structure of drugs used is according to the ABC classification in terms of use value: Grade A accounts for 79.90%, Grade B accounts for 15.04%, Grade C accounts for 5.06%. Among class A drugs, the group of drugs for the treatment of parasites and anti-infectives accounts for 68.90% of the GTSD. The hospital does not use drugs of group AN. Conclusion: The structure of drugs used at Thai Binh Pediatric Hospital in 2020 is relatively reasonable and consistent with the disease model of the Pediatric Hospital. However, the Hospital needs to make adjustments to reduce imported drugs and brand-name drugs accordingly.